Popularitas Calon dan Isu Pilkada Serentak 2020 di Tengah Pandemi Covid-19 Berdasar Kacamata Pengguna Internet di Bandar Lampung (Universitas Medan Area, 2021)
This paper aims to determine the popularity of candidates on the internet through internet user behavioral tendencies (netizens) in surfing and using social media. Second, to find out interest netizens' in two popular issues, namely the 2020 regional elections or the Covid-19 pandemic issue. The author used Habermas' new public sphere theory. Data were collected from internet searches and official social media as primary data, then the data were analyzed using an inductive-descriptive approach with qualitative content analysis techniques, where data were identified and arranged systematically, then abstracted by analyzing one data. With others in depth and concluded as conclusions. This study concludes that netizens in Bandar Lampung had a greater attention to the issue of the Covid-19 pandemic than the issue of the 2020 simultaneous regional elections, as evidenced by tracing around the Covid-19 pandemic issue which was more popular than searches around the Simultaneous Pilkada 2020. This study also concluded that it was still not optimal. The campaign through social media of the three candidate pairs in the 2020 Bandar Lampung Pilkada, was marked by the low tendency of internet users to pay attention to the three candidate pairs on their official social media.